Identification of Cronobacter spp (enterobacter sakazakii) from raw milk and environmental samples of dairy farms - Berhilevych, Oleksandra; Kasianchuk, Victoria (Eastern-European Journal of Enterprise Technologies, 2017)
The aim of this study was to identify the presence of Cronobacter spp (formerly Enterobacter sakazakii) in bulk tank milk and facilities of dairy farms in Sumy Region (Ukraine). A total of 418 samples of bulk tank milk, udder secretion of cows with a subclinical form of mastitis, and environmental samples were collected from 5 local dairy farms of Sumy region (Ukraine). All samples were analyzed for the presence of Cronobacter spp using the United States Food and Drug Administration (FDA) method. Twenty isolates were selected that had typical morphological, cultural and biochemical properties of Cronobacter spp and then they were subjected to a molecular analysis by polymerase chain reaction (PCR) amplification of 16S rRNA. The results indicate that the dairy farm environments, including the cows and the milk are a potential source of Cronobacter in raw milk. This is the first report of Cronobacter spp prevalence in bulk tank milk and environmental samples in the dairy farms of Sumy Region, Ukraine, indicating potential health risk associated with cow’s milk. These data will be valuable for microbiological risk assessment and help authorities to develop strategies to mitigate health risk for humans